Improving the Distribution Policy of the Wage Subsidy Assistance Program (Bantuan Subsidi Upah/BSU) - Tobing, Henriko; Muhyiddin, Muhyiddin; Sari, Ayu Puspita; Rizki, Fika Afiani Ri’fati; Al Ayubbi, Syaefuddin Ahrom (Bappenas Working Papers, 2022)
The purpose of this study is to evaluate the Wage Subsidy Assistance Program (Bantuan Subsidi Upah/BSU) distribution in 2021, which the Government has distributed since August 2021. In contrast to the distribution of BSU in the previous year, this program targets 8.8 million workers with the amount of assistance and criteria slightly different compared to the BSU in 2020. This evaluation becomes important to find out how the process of implementing BSU distribution will be in 2021 and to provide recommendations for improving BSU distribution policies and future policies related to the distribution of similar assistance. Data were obtained from various sources, both primary and secondary. Primary data collection was carried out in five regions, namely the provinces of Banten, West Java, Central Java, Yogyakarta, and East Java, with samples consisting of companies, Labor Offices, Labor Social Security Administering Body (BPJS TK), and Banking operators in the regions. The consideration of the research locus refers to the amount of data on BSU recipients, where Java is the region with the largest number of recipients by region. Secondary data is obtained from various scientific literature and government publication. The qualitative research method using interview guidelines as a data collection tool and root cause analysis matrices as an analytical tool was chosen to get a clear picture of the BSU distribution process in 2021. The findings concluded that the 2021 BSU distribution model was not as good as the 2020 BSU distribution model. There were three main problems within, namely 1) data validity, 2) information services, and 3) bank account opening (Burekol). The suggestions for this study are 1) to change the distribution model, which was originally through individual transfers, to be collective (through companies/institutions) and 2) if continue to use the previous model (Burekol), cooperation between field agencies (Disnaker, regional BPJS TK, and banking branch) is strengthened in an integrated system.